2021
DOI: 10.21203/rs.3.rs-468694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association Between Hypomagnesemia and Severity of Primary Hyperparathyroidism: a Retrospective Study

Abstract: Background: The occurrence of hypomagnesemia in patients with primary hyperparathyroidism (PHPT) has been noted previously; however, the association of hypomagnesemia and severity of primary hyperparathyroidism remains unknown. The present study aimed to evaluate the association of hypomagnesemia with biochemical and clinical manifestations in patients with PHPT.Methods: This was a retrospective study conducted at a tertiary hospital. We obtained data from 307 patients with PHPT from January 2010 through Augus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…The severity was minimal at the first day, and gradually restored from the third day. Similar changes have been reported in patients with PHPT after parathyroidectomy 14,16 . They concluded that PTH might influence magnesium metabolism.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The severity was minimal at the first day, and gradually restored from the third day. Similar changes have been reported in patients with PHPT after parathyroidectomy 14,16 . They concluded that PTH might influence magnesium metabolism.…”
Section: Discussionsupporting
confidence: 86%
“…A highly significant negative correlation between serum calcium and magnesium levels in patients with PHPT was reported in a limited number of older studies 13,14 . Nevertheless, the association of serum magnesium, serum calcium, and PTH has been analyzed in patients with secondary hyperparathyroidism 4,6,15,16 . Fang et al 4 studied the effect of PTH on serum magnesium levels in hemodialysis patients with secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Auch die Ausprägung des primären Hyperparathyreoidismus korrelierte mit dem Magnesiummangel. Zudem hatten die Patient*innen mit Magnesiummangel eine höhere Prävalenz an Osteoporose, Anämie und hyperkalzämischen Krisen (Kalzium>3,5 mmol/l) 19 .…”
Section: Wichtig: Der Einsatz Von Ppi üBer Eine Dauer Von 8 Wochen Hi...unclassified